Traditional foraging for ecological transition? Wild food ethnobotany among three ethnic groups in the highlands of the eastern Hindukush, North Pakistan - Amir Hasan Khan; Muhammad Adil; Muhammad Abdul Aziz; Renata Sõukand; Andrea Pieroni (BMC, 2023)
Abstract Background The Patrak Valley is home to communities, which have been inextricably linked with nature for generations, and local plant knowledge (LPK) represents an important part of their local cultural diversity. In general, globalization has come at the expense of local plant knowledge among several mountain societies, and therefore the current investigation has been undertaken to record the (possibly) last remaining wild food plant/mushroom foraging practices among Pathans, Kohistanis, and Gujjars living in the highlands of the Hindukush, North Pakistan. Methods Data on the uses of wild food plants and mushrooms (WFPs) were collected through 120 semi-structured interviews. The data were cross-culturally compared among the three linguistic groups. Venn diagrams were used to visualize the comparative analysis. To determine the patterns of similarities in plant use among the different ethnic groups, we used the Jaccard similarity index (JI). The recorded data were also compared with the existing Pakistani food ethnobotanical literature. Results A total of 68 WFPs were recorded, the majority of which were used as raw snacks and as cooked vegetables. Fruit was the most frequently reported plant part among the three researched groups. Cross-cultural comparison revealed that 37% of the used plants were commonly shared by the three studied groups. Pathans have retained rich knowledge on WFPs, and they show a comparatively closer affinity with Kohistanis is the use of WFPs compared to Gujjars. While we observed some idiosyncrasies for each of the researched groups, the distinctive plant uses among Gujjars provide insight into their food ecology, their particular human-ecological system centered on mobile pastoralism and their limited exchanges of local food/ecological knowledge due to endogamic patterns. A literature survey revealed some novel or little-known ingredients within Pakistani food ethnobotany/ethnomycology, such as Aesculus indica, Agaricus campestris, Apteranthes tuberculata, Duchesnea indica, Equisetum arvense, Eremurus himalaicus, Isodon rugosus, Morella esculenta, Sophora mollis, and Drimia indica. Conclusion The researched communities have retained important plant knowledge which could be implemented through future development programs considering that most of these traditional foraging practices fulfill environmental and social sustainability standards. Further field studies are required to thoroughly investigate the patterns of foraging among highland pastoral societies in other parts of the Hindukush region and especially their potential for the ongoing ecological transition.